To read Mattelart/Dorfman, 50 years later: but... what about the comics? - Lucas, Ricardo Jorge de Lucena (MATRIZes, 2020)
This text revisits the book Para Ler o Pato Donald, published in 1971, and one of the fundamental titles to start consolidating the name of Armand Mattelart (along with Ariel Dorfman, co-author) in Brazil as a Communication theorist, as well as his later comments and interviews after the work. At a later time, we asked about this (lack of) perception of comics as a kind of “non-object” of research, obscured under the perspective of “cultural imperialism”, under three aspects: the decentralization of Disney production; the problem of translation; and the lack of information on the production of comics in Chile.